The role of leadership in shaping organisational culture in a school in Namibia. - Nangolo, Filemon (Rhodes University, Faculty of Education, Department of Education, 2016)
The purpose of this study was to investigate the role of leadership in shaping the culture of a rural combined school in Oshikoto Region, northern Namibia. This school had previously performed poorly in terms of Grade 10 examination statistics for many years. However, after the appointment of a new Principal, the academic performance of the school has improved tremendously over for the past five years. Having been a teacher, Head of Department, Deputy Principal, Principal, and later an Inspector of Education, I had long held the view that the academic performance of the school depended entirely on the type of leadership the school had. Equally, I have always been aware of the negative impact of the past segregation and the discriminatory education provided by the colonial masters in South Africa and South West Africa/Namibia. The poor education provided to South Africans and the then South West Africa /Namibia posed a serious challenge to the leadership and management of schools as the majority of Principals, if not all, were poorly and inadequately trained to provide the necessary skills needed for one to be a successful Principal. Given this background, I tried to use a case study to explore the role of leadership in shaping the culture of the organisation. Research suggests that there is a strong relationship between organisational culture and school effectiveness. This study was guided by Schein's three levels of organisational culture namely artifacts, espoused values and basic assumptions (Schein, 1992, p. 17). From these arise the following research questions: What do artifacts (symbols, structures, procedures and policies) reveal about the school culture? What are the espoused values shaping the school culture? What basic assumptions underpin the leadership of the school culture? How does leadership contribute to the creation and maintenance of a positive organisational culture at a school? The data was collected by using three different data collection methods namely, observation, document analysis and interviewing different people who hold leadership positions in the school. These were the Principal, a Head of Department, School Board chairperson, a teacher in the school management team (SMT) and a class monitor. With regard to data analysis, I first immersed myself in the data and I developed themes that formed the basis of my discussion with my research questions in mind. The analysis revealed that leadership plays a pivotal role in shaping the culture at the case study school. However, it emerged that despite the existence of a strong culture at the case study school, as with all other organisations, there are some challenges that limit the school to realise its goal of 100 % A-B symbols in all subjects.
Keywords: Uncatalogued